Estimation of p, p'-DDT degradation in soil by modeling and constraining hydrological and biogeochemical controls. (August 2018) - Sanka, Ondrej; Kalina, Jiri; Lin, Yan; Deutscher, Jan; Futter, Martyn; Butterfield, Dan; Melymuk, Lisa; Brabec, Karel; Nizzetto, Luca
Abstract: Despite not being used for decades in most countries, DDT remains ubiquitous in soils due to its persistence and intense past usage. Because of this it is still a pollutant of high global concern. Assessing long term dissipation of DDT from this reservoir is fundamental to understand future environmental and human exposure. Despite a large research effort, key properties controlling fate in soil (in particular, the degradation half-life (τsoil )) are far from being fully quantified. This paper describes a case study in a large central European catchment where hundreds of measurements of p, p'-DDT concentrations in air, soil, river water and sediment are available for the last two decades. The goal was to deliver an integrated estimation of τsoil by constraining a state-of-the-art hydrobiogeochemical-multimedia fate model of the catchment against the full body of empirical data available for this area. The INCA-Contaminants model was used for this scope. Good predictive performance against an (external) dataset of water and sediment concentrations was achieved with partitioning properties taken from the literature and τsoil estimates obtained from forcing the model against empirical historical data of p, p'-DDT in the catchment multicompartments. This approach allowed estimation of p, p'-DDT degradation in soil after taking adequate consideration of losses due to runoff and volatilization. Estimated τsoil ranged over 3000–3800 days. Degradation was the most important loss process, accounting on a yearly basis for more than 90% of the total dissipation. The total dissipation flux from the catchment soils was one order of magnitude higher than the total current atmospheric input estimated from atmospheric concentrations, suggesting that the bulk of p, p'-DDT currently being remobilized or lost is essentially that accumulated over two decades ago. Graphical abstract: Image 1 Highlights: Hydrobiogeochemical-multimedia fate model was applied in a large river catchment. p, p'-DDT half-life in soil was estimated to be 3000–3800 days. More than 90% of the total p, p'-DDT dissipation was attributed to degradation. Total dissipation flux was 10 times higher than the total current atmospheric input. Abstract : This study assesses biogeochemical controls on p, p'-DDT environmental fate, and estimates its degradation half-life in soil based on record of hundreds of historical soil concentrations.